37. Positive Psychopathology in Exceptionally Creative Artists? - Knudsen, Kendra (Schizophr Bull, 2017)
Background: As part of a broad investigation of brain and behavior, the UCLA Big C Project studied whether “Big C” (world-class) artistic and scientific creativity is linked with schizotypal and autistic features and whether temperamental traits are associated with creativity. Methods: With the Schizotypal Personality Questionnaire (SPQ), Social Responsiveness Scale (SRS), and the International Personality Item Pool Representation of the NEO PI-R (IPIP-NEO), we examined more than 30 individuals each in 3 groups: Big C Visual Artists (VA), Big C Scientists (SCI), and a Smart Comparison Group (SCG) matched on age, sex, race/ethnicity, parental education, and IQ estimates. Big C groups had internationally prominent creative reputations and markedly higher Creative Achievement Questionnaire scores within their domains. Results: VA reported higher levels of odd beliefs, ideas of reference, unusual perceptions, odd speech, and more socially divergent tendencies. Specifically, VA had significantly greater scores in Cognitive/Perception and Disorganization SPQ factors compared to SCI (and nominally greater scores than SCG). VA also had significantly higher scores in SRS subscales of Social Communication, Social Motivation, Restricted Interests and Repetitive Behavior compared to SCG. All 3 groups had significant differences in openness (VA>SCI>SCG). Both Big C groups were significantly more achievement striving than SCG, with the scientists higher than the visual artists (SCI, VA > SCG). The Big C groups also reported significantly higher scores on activity and liberalism compared to SCG; the visual artists were higher than the scientists on these facets (VA, SCI > SCG). VA had significantly higher scores on imagination and artistic interests than SCI and SCG (VA > SCI, SCG). Conclusion: These results complement and extend past findings of high magical ideation and openness associated with everyday creative achievement in healthy individuals. Compatible with the hypothesis of “subclinical” psychopathology associated with creativity, these results also open questions about whether there are valuable and potentially adaptive aspects of psychopathological traits and what may be driving this association in exceptional artistic creativity. These results also suggest that openness, imagination, and an active, achievement-focused lifestyle may mediate this link.